Dynamic Depositor Discipline in U.S. Banks - McDill, Kathleen (IMF Working Papers; Working Paper, 2003)
This paper investigates the presence of depositor discipline in the U.S. banking sector. We test whether depositors penalize (discipline) banks for poor performance by withdrawing their uninsured deposits. While focusing on the movements in uninsured deposits, we also account for the possibility that banks may be forced to pay a risk premium in the form of higher interest rates to induce depositors not to withdraw their uninsured deposits. Our results support the existence of depositor discipline: a weak bank may not necessarily be able to stop a deposit drain by raising its uninsured deposit interest rates.